2021
DOI: 10.21037/qims-21-87
|View full text |Cite
|
Sign up to set email alerts
|

Age-related magnetic susceptibility changes in deep grey matter and cerebral cortex of normal young and middle-aged adults depicted by whole brain analysis

Abstract: Background: Iron accumulates in brain tissue in healthy subjects during aging. Our goal was to conduct a detailed analysis of iron deposition patterns in the cerebral deep grey matter and cortex using region-based and whole-brain analyses of brain magnetic susceptibility. Methods: Brain MRI was performed in 95 healthy individuals aged between 21 and 58 years on a 3T scanner. MRI protocol included T1-weighted (T1W) magnetization-prepared rapid acquisition with gradient echo images and 3D flow-compensated multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 47 publications
2
25
2
Order By: Relevance
“…Healthy controls (HC) for brain MRI were recruited from the general community [ 15 ]. The controls were free of neurologic or other medical disorders affecting brain health and had a normal neurological examination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthy controls (HC) for brain MRI were recruited from the general community [ 15 ]. The controls were free of neurologic or other medical disorders affecting brain health and had a normal neurological examination.…”
Section: Methodsmentioning
confidence: 99%
“…MRI examination was performed and processed as previously published [ 15 ]: Magnetization Prepared Rapid Gradient-Echo (MPRAGE, TE: 2.96 ms, TI 900 ms TR: 2300 ms, spatial resolution: 1 × 1 × 1 mm), gradient-echo (GRE, 6 TEs: 4.5–29.5 ms, evenly spaced, TR: 33 ms, spatial resolution: 0.94 × 0.94 × 0.94 mm), and Fluid-Attenuated Inversion Recovery (FLAIR, TE 397 ms, TI 1800 ms, TR 5000 ms, spatial resolution 1 × 1 × 1 mm) pulse sequences were acquired on a 3T MRI scanner (Siemens Skyra 3T, Siemens Healthcare, Erlangen, Germany) with a 20 channel head coil.…”
Section: Methodsmentioning
confidence: 99%
“…Fe accumulation with age predominantly takes place in basal ganglia and other brain regions concerned with motor functions. During adult lifespan, the steepest accumulation is observed in the red nucleus, substantia nigra (SN), and putamen [7,8]. Whole-brain MRI studies showed that, in addition to the deep gray matter, precentral, prefrontal, and occipital cortices involved in motor, cognitive, and visual function also accumulate iron with aging [7,9] (Table 1).…”
Section: Brain Iron Neuroinflammation and Cognitive Decline In Agingmentioning
confidence: 99%
“…During adult lifespan, the steepest accumulation is observed in the red nucleus, substantia nigra (SN), and putamen [7,8]. Whole-brain MRI studies showed that, in addition to the deep gray matter, precentral, prefrontal, and occipital cortices involved in motor, cognitive, and visual function also accumulate iron with aging [7,9] (Table 1). Glial cells (astrocytes, oligodendrocytes, microglia) contain higher Fe concentrations than neurons whereby astrocytes are the primary Fe homeostatic cells in the central nervous system.…”
Section: Brain Iron Neuroinflammation and Cognitive Decline In Agingmentioning
confidence: 99%
See 1 more Smart Citation